2016
DOI: 10.3892/etm.2016.3214
|View full text |Cite
|
Sign up to set email alerts
|

ROCK2 mediates the proliferation of pulmonary arterial endothelial cells induced by hypoxia in the development of pulmonary arterial hypertension

Abstract: Abstract. It has been reported that RhoA activation and Rho-kinase (ROCK) expression are increased in chronic hypoxic lungs, and the long-term inhibition of ROCK markedly improves the survival of patients with pulmonary arterial hypertension (PAH). However, whether Rho-kinase α (ROCK2) participates in regulation of the growth of pulmonary arterial endothelial cells (PAECs) remains unknown. The aim of the present study was to investigate the effect of hypoxia on the proliferation of PAECs and the role of ROCK2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Proliferation in pulmonary artery EC cultures induced by hypoxia involves the increase in cyclin A and cyclin D1 in order to promote cell cycle progression. Under these conditions, the use of Y-27632 or a small-interfering RNA targeting ROCK2 abolished EC proliferation without compromising cell viability, indicating that ROCK inhibition may also control EC phenotypic changes seen in PH [ 68 ]. These effects could reflect ROCK activation by vascular growth factor and EC stiffening, as ROCK inhibitors also block EC migration and angiogenesis [ 69 , 70 , 71 ].…”
Section: Cellular Effects Of Rock On the Cardiovascular Systemmentioning
confidence: 99%
“…Proliferation in pulmonary artery EC cultures induced by hypoxia involves the increase in cyclin A and cyclin D1 in order to promote cell cycle progression. Under these conditions, the use of Y-27632 or a small-interfering RNA targeting ROCK2 abolished EC proliferation without compromising cell viability, indicating that ROCK inhibition may also control EC phenotypic changes seen in PH [ 68 ]. These effects could reflect ROCK activation by vascular growth factor and EC stiffening, as ROCK inhibitors also block EC migration and angiogenesis [ 69 , 70 , 71 ].…”
Section: Cellular Effects Of Rock On the Cardiovascular Systemmentioning
confidence: 99%
“…In addition, ROCK regulates EC proliferation by its targeted gene expression associated with cell cycle. In the hypoxic condition, ROCK2 promotes proliferation of pulmonary arterial ECs though upregulating the expression of cyclin A and cyclin D1 101. Rho/ROCK signaling mediates oxLDL-induced EC proliferation through downregulation of cell cycle inhibitor p27 102.…”
Section: Rock In Fundamental Stages Of Angiogenesismentioning
confidence: 99%
“…FENG QIAO et al . 14 showed that the activity of endothelial cells decreased after using siRNA to silence the ROCK2 gene. At the same time, they found that under low oxygen, Rho/Rho-kianse pathway was activated, ROCK2 promoted cell division phase G0/G1 phase to S phase by Up-regulated A/D1 cell cycle protein expression to shorten cell cycle and promote endothelial cell proliferation.…”
Section: Discussionmentioning
confidence: 99%